Kitâb mu’cemü’l-büldân - 880-01 Yâkût el-Hamevî, 1179-1229. (Kahire Kahire Kahire)
10 cilt 6 ciltte (1. c. 398 sayfa, 2. c. 446 sayfa ; 3. c. 503 sayfa ; 4. c. 467 sayfa ; 5. c. 445 sayfa, 6. c. 416 sayfa ; 7. c. 347 sayfa, 8. c. 536 sayfa ; 9. c. 392 sayfa, 10. c. 360 sayfa)